3D Objects Localization Using Fuzzy Approach and Hierarchical Belief Propagation: Application at Level Crossings. (20th October 2010) - Fakhfakh Fakhfakh, N. N.; Khoudour Khoudour, L. L.; El-Koursi El-Koursi, E. E.; Bruyelle Bruyelle, J. L. J. L.; Dufaux Dufaux, A. A.; Jacot Jacot, J. J.
Abstract : Technological solutions for obstacle-detection systems have been proposed to prevent accidents in safety-transport applications. In order to avoid the limits of these proposed technologies, an obstacle-detection system utilizing stereo cameras is proposed to detect and localize multiple objects at level crossings. Background subtraction is first performed using the color independent component analysis technique, which has proved its performance against other well-known object-detection methods. The main contribution is the development of a robust stereo-matching algorithm which reliably localizes in 3D each segmented object. A standard stereo dataset and real-world images are used to test and evaluate the performances of the proposed algorithm to prove the efficiency and the robustness of the proposed video-surveillance system.